THE FUTURE OF SUSTAINABLE RURAL TOURISM DEVELOPMENT– THE IMPACTS OF CLIMATE CHANGE - Martin Zsarnoczky (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2017)
Climate change a phenomenon mainly caused by the high level of greenhouse gas (GHG) emissioninto the atmosphere of the Earth - makes human ecosystems vulnerable and is predicted to affect oureveryday life in the near future. The increased intensity of storms, cyclones, drought and flooding; thegreater magnitude and frequency of heat and cold waves and the continuous rise of the sea-level are likelyto generate more geopolitical conflicts, especially in the most vulnerable regions of the planet. The threemain categories of climate change impacts are classified as environmental, economic and social effects.The economic and social consequences of climate change are expected to significantly reduce the resilienceof rural tourism regions and their capability to successfully respond to other possible critical events. Dueto the impacts of natural disasters and extreme climatic events, global climate change affects Europeanrural regions, too. The development of sustainable rural tourism requires the in-depth understanding of theongoing processes and the development of tools that will serve the interest of tourism and local people alike.